bla(NDM-1) Is a Chimera Likely Constructed in Acinetobacter baumannii - Toleman, M. A. (American Society for Microbiology, 2012)
Alignment of DNA sequences found upstream of aphA6 and all bla(NDM-1) genes displays 100% identity. This identity continues 19 bp into the bla(NDM-1) gene such that the first 6 amino acids of aphA6 and bla(NDM-1) are the same. Furthermore, the percent GC content (GC%) of aphA6 is considerably lower than that of bla(NDM-1) and the GC% within the bla(NDM-1) structural gene changes dramatically after the first 19 bp. This is unequivocal evidence that bla(NDM-1) is a chimera.